An integrative review of nursing staff experiences in high secure forensic mental health settings: Implications for recruitment and retention strategies. (19th September 2020) - Oates, Jennifer; Topping, Alice; Ezhova, Ivanka; Wadey, Emma; Marie Rafferty, Anne
Abstract: Aims: To identify the experiences of nursing in high secure forensic mental health settings that may affect staff recruitment and retention. Background: Recruitment and retention of Registered Nurses is a vital international concern in the field of mental health. The high secure forensic setting presents unique challenges for the nurse. Studies of nurse's experiences in this setting have not previously been reviewed in the context of workforce sustainability pressures. Design: An integrative review (Whittemore and Knapfl, 2005). Data sources: A systematic search of data sources: MEDLINE (PubMed), PsycINFO, EMBASE, CINAHL, International Bibliography of the Social Sciences, Applied Social Sciences Index and Abstracts (ASSIA), Social Services Abstracts, ProQuest Social Sciences Premium collection (IBSS, PAIS, and Sociological Abstracts), and Web of Science from inception to December 2019. Review methods: Data extraction, quality appraisal, and convergent qualitative synthesis. Results: Fifteen papers were selected for inclusion in the review, describing 13 studies. Six studies were quantitative, all cross‐sectional surveys. There were seven qualitative studies, using a variety of methodologies. Four themes were identified: engagement with the patient group, the ward social environment, impact on the nurse, and implications for practice. Conclusion: When policymakers address workforce shortages in high secure forensic nursing they must take account of the unique features of the setting and patient group. Nurses must be adequately prepared and supported to function in an ethically and emotionally challenging environment. Impact: This study identified factors affecting workforce pressures in the speciality of forensic mental health nursing. Findings are of interest to national nursing policymakers and workforce leads in mental health service provider organizations, seeking to promote forensic nursing as a career option and retain nursing staff. 摘要: 目标: 了解在高安全性司法心理健康环境中的护理人员经验, 可能会对护士的招聘和留用产生影响。 背景资料: 招聘和留用注册护士是精神卫生领域的一个重要的国际问题。高安全性司法环境对护士提出了独特的挑战。以往并未在员工可持续性压力的背景下对此种环境下的护士经历进行过研究回顾。 设计: 综合回顾(怀特莫尔和克诺普夫勒, 2005年)。 数据来源: 数据来源的系统性搜索:联机医学文献分析和检索系统(国际文献数据库(PubMed))、心理学文摘(PsycINFO)、荷兰医学文摘数据库(Embase)、护理学数据库(CINAHL)、国际社会科学杂志、应用社会科学索引与摘要(ASSIA)、社会服务学文摘 、ProQuest社会科学特选系列(IBSS、PAIS和社会学摘要)以及科学网从成立之初至2019年12月的内容。 评审方法: 数据提取、质量评估和收敛性定性合成。 结果: 回顾中纳入了15篇论文, 对13篇研究做出了描述。六篇研究为采取横断面分析的定量调查。七篇定性研究采取了多种方法论。确定了四大主题:与患者群体的接触、病房的社会环境、对护士的影响以及对实践的影响。 结论: 当决策者解决高安全性法医护理的人员短缺问题时, 他们必须考虑到环境和患者群体的独特特征。护士必须做好充分的准备和支持, 以便在具有伦理和情感挑战的环境中发挥作用。 影响: 本研究旨在探讨影响司法心理健康护理专业员工压力的因素。国家护理政策制定者和精神卫生服务提供者组织的负责人员都对这些研究发现深感兴趣, 便于他们寻求出将法医护理作为一种职业选择, 并留住护理人员的方法。